2008
DOI: 10.1111/j.1556-4029.2008.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

STR Profiles from DNA Samples with “Undetected” or Low Quantifiler™ Results

Abstract: Screening methods capable of identifying DNA samples that will not yield short tandem repeat (STR) profiles are desired. In the past, quantitation methods have not been sensitive enough for this purpose. In this study, low level DNA samples were used to assess whether Quantifiler has a minimum quantitation value below which STR profiles would consistently fail to be detected. Buccal swabs were obtained and the DNA extracted, quantified, and serially diluted to concentrations ranging from 0.002 to 0.250 ng/micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
1
21
1
2
Order By: Relevance
“…Samples with negative human DNA results and normal IPC Cq values may still produce full STR profiles without additional purification of the sample [34]. Another study reported 27% of low-quantity samples with "undetermined" quantification values tested produced at least partial STR profiles [35]. These observations are important to relate to samples that may contain PCR inhibitors, as inhibition effectively decreases the amplifiable concentration of a DNA sample.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…Samples with negative human DNA results and normal IPC Cq values may still produce full STR profiles without additional purification of the sample [34]. Another study reported 27% of low-quantity samples with "undetermined" quantification values tested produced at least partial STR profiles [35]. These observations are important to relate to samples that may contain PCR inhibitors, as inhibition effectively decreases the amplifiable concentration of a DNA sample.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…The very first technique (i.e. restriction fragment length polymorphism (RFLP) analysis) required large amounts of DNA to create individual genetic profiles [2], however the advent of highly sensitive PCR multiplex assays has markedly reduced that amount, insomuch that DNA deemed "undetectable" during quantification may still yield complete genetic profiles [3].…”
Section: Dna Typing Techniques and Contaminationmentioning
confidence: 99%
“…When using qualitative threshold-based methods, they seek criteria for processing only those samples having enough DNA to elevate data peaks above threshold [18], [56]. Another strategy is to report only genotype matches for major contributors to a mixture [12].…”
Section: Discussionmentioning
confidence: 99%